Conjugated 5-fluorouracil with mitochondria-targeting lipophilic cation: design, synthesis and biological evaluation12. Issue 10 (11th August 2016) - Wang, Jia; Fan, Xiao-Yang; Yang, Li-Yun; He, Huan; Huang, Rong; Jiang, Feng-Lei; Liu, Yi
Abstract : 5-Fluorouracil (5-FU) was linked with mitochondria-targeting lipophilic cation F16 by three kinds of vulnerable bonds. Abstract : 5-Fluorouracil (5-FU) was linked with F16 by vulnerable bonds to selectively target cancer mitochondria which resulted in conjugated compounds, including F16–5-FU, F16–OOC-FU, F16–NHOC-FU and F16–SS-FU. F16–OOC-FU decreased the antiproliferative activity of 5-FU on the nontumor cell line, and the cytotoxicity of F16–SS-FU significantly increased when administered with dithiothreitol (DTT).